Biodiversity and Soil Characterization of Ancestral Domain of the Tagbanua Tribe in Aborlan, Palawan, Philippines - Reynald M. Quilang (Nature Environment and Pollution Technology)
This study was conducted to determine strategies to enhance the sustainable forest management practices of the Tagbanua tribe. Specifically to describe the biodiversity and soil characteristics of the ancestral domain. The modified belt-transect method for biodiversity assessment developed by B+WISER (2014), further modified by the Department of Environment and Natural Resources (DENR) in the assessment, was used in this study. Results of soil chemical analysis showed significant variations among various land uses. The ancestral domain had at least 73 plant species belonging to 34 families and 59 genera. Four (4) taxa whose SN/families were still undetermined and another three (3) genera under families Annonaceae, Meliaceae, and Sapindaceae were unidentified. It had 12 plant species that are threatened with one critically endangered based on the list of threatened Philippine plants of the DENR. On the other hand, a total of 372 birds representing 61 species from 29 families were recorded. The high Shannon-Weiner Diversity Index (H’=3.69) and Shannon’s Evenness (HE=0.90) values indicate high avifaunal diversity and equitable distribution among the detected species. Most of the conservation priority species recorded in the area are Palawan endemic species. The survival of these birds is threatened by extinction due to habitat loss. This observation emphasized the importance of the ancestral domain as a refuge for these endemic species and conservation priority areas.